ANALISIS HAMBATAN GURU MIPA DALAM PEMBELAJARAN DARING DI SMAS KR. RANTEPAO DI MASA PANDEMI COVID 19 - D. B. Sae; H. Sihotang (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2020)
This study was to desribe the obstacles of Mathematics and Natural Sciences teachers at Christian Senior High School Rantepao in online learning during the Covid-19 pandemic. The study was a qualitative approach with descriptive analysis. Subjects in this study were 17 Mathematics and Natural Sciences teachers at Christian High School Rantepao. Data collection techniques using a questionnaire. The data were analized by descriptive percentage. The results of this study showed that Mathematics and Natural Sciences teachers at Christian Senior High School Rantepao experienced obstacles in online learning in the Covid-19 pandemic. Keywords: covid-19, , online learning, teacher, obstacles.